The Effect of Price, Product Variation, and Word of Mouth on Consumer Purchase Decisions at the Cahaya Wirama Store, Selats Branch, Karangasem - Ni Luh Ayu Eka Widayanti; I Ketut Johny Pramanda Putra; I Gusti Ayu Athina Wulandari (Journal of Governance, Taxation and Auditing, 2026)
This study aims to examine and analyze the effects of price, product variety, and word of mouth on purchasing decisions. This study was conducted at the Cahaya Wirama Store, Selat Branch, Karangasem, with a sample of 170 respondents. All data obtained from the questionnaire distribution were subsequently analyzed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS). The results of the study indicate that (1) Price, product variety, and word of mouth simultaneously have a significant effect on consumer purchasing decisions at the Cahaya Wirama Store, Selat Branch, Karangasem; (2) Price has a positive and significant effect on consumer purchasing decisions at the Cahaya Wirama Store, Selat Branch, Karangasem; (3) Product variety has a positive and significant effect on consumer purchasing decisions at the Cahaya Wirama Store, Selat Branch, Karangasem. (4) Word of mouth has a positive and significant effect on consumer purchasing decisions at the Cahaya Wirama Store, Selat Branch, Karangasem.